The Impact of Care Upon Alzheimer Patient’s Family Caregiver in Sulaimani City - Farida Abdulqadir Tahir (Kurdistan Journal of Applied Research)
Family Care giving for relatives with Alzheimer, often includes assisting them with one or more activities of daily living, as Alzheimer is one of the progressive impairment diseases in patient’s physical and cognitive ability. The aim of this study is to assess the effect of being a family caregiver of Alzheimer patients in Sulaimani city. A cross-sectional quantitative study carried out among family members who care for older patients with Alzheimer’s disease. The instrument was designed and constructed by the researcher through an intensive review of the literature and also through a series of meeting survey with caregivers in order to measure the variables underlying the present study. The data were obtained by the researcher, who interviewed families, structured questionnaire forms filled out with a total of 100 families. These were taken using a random sample of those families have Alzheimer’s problem in Sulaimani city. The majority of participants were women with a mean age 53.75 years old, married, housewives and with university education. More than half of the Caregiver was suffered from moderate to severe burdens.  Rotated Component Matrix was used to get the level of effectiveness by a series of components according to the important effects of the variables on Alzheimer disease. The researcher found that the financial burden has taken the first order, followed by psychological and then a social burden. The finding of the study shows a significant relationship between some demographic characteristics and the three dimensions of the burden. It appears that financial factor is in the first rank by a total variance (85.151), then psychological factors by a total variance (81.532) then the social factor by total variance (65.851). Financial factor was the strongest factor that impacted their family income. Some psychosocial oriented services are recommended for the caregivers in order to decrease the stress and help them to adapt to the situation. Some educational programs are also required to facilitate providing enhanced physical and psychological care. This study also recommends allocating salary for every patient to ease the financial burden on the caregivers